First record of Oldenlandia corymbosa (Spermacoceae-Rubiaceae), a new alien species for Paraguay and Argentina - Mariela Nuñez Florentin (Boletín de la Sociedad Argentina de Botánica, 2022)
Background and aims: During the revision of the southern South American species of Oldenlandia, populations of O. corymbosa were found in Paraguay and Argentina. The aim of this contribution is to report the presence of this adventitious species to the Paraguayan and Argentinian flora for the first time.